MASALAH BELAJAR YANG DIALAMI SISWA SELAMA BELAJAR DARING DI MASA PANDEMI COVID 19 - Izmi, Nur; Tampubolon, Budiman; Salimi, Asmayani (Universitas Tanjungpura, 2023)
This study aims to describe the problems faced by students whilestudying at home during the Covid-19 pandemic for Class VIstudents at the State Elementary School 10, East Pontianak. Theresearch method used is a descriptive method with a qualitativeresearch form. The data sources of this research are the sixth-gradestudents of State Elementary School 10, East Pontianak. Thisresearch data is in the form of interviews and questionnaires aboutobstacles in the implementation of thematic learning during thecovid-19 pandemic. The results of the analysis show First, there arestill many teachers who do not conduct context analysis beforemaking lesson plans, do not analyze the learning media used, do notcoordinate with other teachers and do not provide feedback tostudents. Second, WhatsApp and Google Classroom are the mostwidely used applications as learning media. Third, there are severalobstacles experienced by teachers and students during theimplementation of online learning, namely internet access andquotas. Fourth, schools need to provide support to teachers andstudents, especially in providing internet access. Fifth, both studentsand teachers miss face-to-face learning activities directly.